The clinical and electrophysiological investigation of tremor. (April 2022) - Deuschl, Günther; Becktepe, Jos S.; Dirkx, Michiel; Haubenberger, Dietrich; Hassan, Anhar; Helmich, Rick C.; Muthuraman, Muthuraman; Panyakaew, Pattamon; Schwingenschuh, Petra; Zeuner, Kirsten E.; Elble, Rodger J.
Highlights: This chapter provides an overview of clinical and electrophysiological tools for measuring and classifying tremor. The distinguishing clinical and electrophysiologic features of the different forms of tremor are explained. The pathophysiology of the different tremors is reviewed with an emphasis on electrophysiological methods. Abstract: The various forms of tremor are now classified in two axes: clinical characteristics (axis 1) and etiology (axis 2). Electrophysiology is an extension of the clinical exam. Electrophysiologic tests are diagnostic of physiologic tremor, primary orthostatic tremor, and functional tremor, but they are valuable in the clinical characterization of all forms of tremor. Electrophysiology will likely play an increasing role in axis 1 tremor classification because many features of tremor are not reliably assessed by clinical examination alone. In particular, electrophysiology may be needed to distinguish tremor from tremor mimics, assess tremor frequency, assess tremor rhythmicity or regularity, distinguish mechanical-reflex oscillation from central neurogenic oscillation, determine if tremors in different body parts, muscles, or brain regions are strongly correlated, document tremor suppression or entrainment by voluntary movements of contralateral body parts, and document the effects of voluntary movement on rest tremor. In addition, electrophysiologic brain mapping has been crucial in our understanding of tremor pathophysiology. The electrophysiologic methods of tremor analysis are reviewed in the context of physiologic tremor and pathologic tremors, with a focus on clinical characterization and pathophysiology. Electrophysiology is instrumental in elucidating tremor mechanisms, and the pathophysiology of the different forms of tremor is summarized in this review.